ToGouR: Tour Guide Robot Visualization using Shape Recognition Pattern for Automatic Navigation - Sulaiman, Hamzah Asyrani; Meor Said, Maizatul Alice; Ismail, Mohd Muzafar; Pazil, Muhamad Arif; Akmal Subari, Ahmad Zulfadhli (2013)
The invention of autonomous robots with an increasing demand for industrial used has been caught attention from researchers and inventors. In this new sophisticated era, various types of robots and systems have been developed and bring significant contribution to the industries, economy, and infrastructure. Thus in this project, we have develop an application for PIC based Tour Guide Robot (ToGouR) where the PIC16F877A has been chosen as the main microcontroller. The application has a Graphical User Interface (GUI) has allows the user to interact in interactive ways between ToGouR and the images for navigation systems. The application also has an ability to perform shape recognition for path planning and automatically make alternative ways when various shapes that have been recognized are put in the way. Various alternatives have been used to make sure this project is successful carried out. This tour guide robot is suitable to be commercialized with numerous robotics companies that would like collaborate in delivering this project as a product and can be used for military or during any unexpected catastrophe such as one that occurred in Japan.